Language Matters : Inequality amongst the Sámi Minority in Norway & Sweden - Kupisch, Tanja; Lloyd-Smith, Anika; Bergmann, Fabian; Yasar, Rusen (2023)
Members of the Sámi minorities in Norway and Sweden who identify with their native culture experience discrimination, especially when they use the Sámi language in public. While this is true in both countries, a comparison shows that specific minority policies affect the level of inequality. Spending more on the enhancement of Sámi language and culture—as Norway does—leads to a higher level of (self)esteem and equality published